DESIGN AND BUILD OF THE TWILIGHT SKY BRIGHTNESS MONITORING SYSTEM - Arifin Dobson, Muhammad
Twilight is a transition between day and night, there are three main phases in this transition period. It has been known that the main contributor of Twilight’s sky brightness is the Sun rising through the horizon. In reality, the variability and the apparent sky brightness contributed by weather condition, amount of particles in the atmosphere make each Twilight a unique phenomenon with it’s own specific sky brightness and colours. The aim of this thesis is to design and built a remote monitoring system that can be deployed in remote areas and still can be accessed through the internet. The system will collect data in a long period of time to increase the temporal resolution of data. Environmental and power sensor will be installed in the system to give an additional parameter for the light curve analysis. Through combining Sky Quality Meter (SQM) and a CMOS camera as the main sky brightness sensor, the system has collected some data and showing there are interesting features in the light curve gathered from the pilot survey program. The linearity of SQM and the camera has a promising potential for further data analysis and radiometric calibration. Results shown there are novel feature from the effect of Moonlight, weather and light pollution in the characteristic of the sky brightness light curve, some data shows a lag time in the color light curve captured by the camera near the time of the sun rising. The system will continue the survey and collect more data on the Twilight’s sky brightness.